The Crime of Prohibited Financing of Political Organizations - Sandoval, Juan Carlos (2022)
This article is a first approach to the study of criminal figures related to the corrupt financing of political parties in Peru. To this end, the text focuses on the analysis of the basic modality of the crime of prohibited financing of political organizations (CP, art. 359-A), which was created by virtue of Law 30997, of August 5, 2019, and that punishes, in short, those who request, accept, deliver or receive financial resources from prohibited sources to benefit a political organization. The incrimination of this conduct is not an isolated case in comparative law, so the work begins with a review of the international anti-corruption policy to determine the state of the art in the fight against the phenomenon of corruption in economic and financial functioning of political parties. Next, some critical considerations are formulated on the treatment provided by both the Constitution and Law 28094, on political organizations, of November 1, 2003, to the problem of the economic support of political parties. The previous topics provide the conceptual and normative bases that allow a better understanding of the elements of the object type and the subjective type of the crime typified in the article 359-A of the Penal Code. This contribution ends with the exposition of the main conclusions that have been reached.